2004
DOI: 10.1080/02508281.2004.11081448
|View full text |Cite
|
Sign up to set email alerts
|

NGOs in Tourism and Preservation Democratic Accountability and Sustainability in Question

Abstract: I Research Probe I ' !his sec_~on has been sp~cifically intr_odu~ed to inclu~e findings of special significance and problem areas of subtle nuances m tour:sm resear~h. Insrghiful cantribuhons presentmg the state-of-the-art preferably from the developing societies will be app:ecrated. It W!ll also encourage schola.rs .and aut~ors to think against the grain, probing the consistency of theoretical notwns and research trends whose heunstrc value !S all too often taken for granted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Some authors showed that projects may yield social benefits, even where they fail to achieve conservation goals [107, 113]. Some showed that projects may improve the local sense of ownership and environmental awareness, even if they fail to deliver expected economic returns [85, 96, 97, 99]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors showed that projects may yield social benefits, even where they fail to achieve conservation goals [107, 113]. Some showed that projects may improve the local sense of ownership and environmental awareness, even if they fail to deliver expected economic returns [85, 96, 97, 99]. …”
Section: Resultsmentioning
confidence: 99%
“…Few of these case studies, however (S3 Table), quantified the conservation outcomes of NGO-based ecotourism projects accurately or precisely [57, 81, 83, 85, 9396, 99, 105, 106, 120, 122, 123]. Four mechanisms were identified.…”
Section: Resultsmentioning
confidence: 99%
“…non-profit organizations, as one of the stakeholders in the successful development of tourism (Hassan, 2000;Swarbrooke, 2001;Araujo, Bramwell, 1999;Jamal, Stronza, 2009;Ellis, Sheridan, 2014. ) According to Farmaki (2015) and Liburd (2004), the widening of associations' activities is a milestone in tourism because associations have the ability to reduce the gap between different social classes by including different approaches and sustainable tourism practices. Given that, it can be assumed that associations have the creative potential and flexibility needed for initiatives in sustainable tourism development.…”
Section: Associations' Relations To Tourismmentioning
confidence: 99%
“…The term "fundraising" has many different meanings but it most commonly refers to the idea of gathering resources from different donors. In its broadest sense, fundraising is a process which enables access to necessary funds in order to secure the flow of income that will ultimately enable the maintenance of nonprofit organizations' activities (Lewinsky, Muharemović, 2011). Defined like that, fundraising refers to all activities carried out in a non-profit organization to provide resources necessary for its sustainability and the implementation of its mission.…”
Section: Introductionmentioning
confidence: 99%
“…According to Fisher (1993) and Liburd (2004) the expansion of NPOs activities represents a turning point for tourism because of their capability to reduce the gap between different strata of society by involving different approaches and encouraging sustainable tourism activities. NPOs have the creative potential and flexibility in the initiatives of sustainable tourism development (Dabphet, 2012).…”
mentioning
confidence: 99%